PERENCANAAN REAKTOR LUMPUR IPAL DOMESTIK MOJOSONGO SURAKARTA - Sutrisno, Endro; Budisulistiorini, Sri Hapsari (Universitas Diponegoro, 2010)
Increasing of the number of society and development for the residential facilities has resulted problem such as domestic wastewater. One of Domestic WWTP in Surakarta is Mojosongo WWTP. It serves house connections which lies in northern of Surakarta. It includes some units, those are inlet, first settling, aerated lagoon I, aerated lagoon II, second sedimentation, and sludge drying bed. The treatment represents for the environmental treatment and to avoids the presence of pollution. It will result effluent where has required standard regulation for wastewater and sludge. The sludge there becomes problem because it is just thrown to the final disposal. Therefore, one of the right treatment is to recycle sludge using composting. Recycling the sludge will also give benefit to PDAM as the stakeholder of WWTP. Sludge resulted in a month is 20,54 m3. Raw materials used for composting are sludge, organic garbage, and saw invade with ratio 0,05: 1: 0,025. Product composting resulted is 7,3 m3/day and using 1200 m3 area. Units of composting there includes receiving space, composting reactor, filtering and packaging, warehouse, and garage.